2008
DOI: 10.1097/rti.0b013e3181804763
|View full text |Cite
|
Sign up to set email alerts
|

Focal Increased Activity in the Liver on 18F-FDG PET Scan Secondary to Brachiocephalic Vein and Superior Vena Cava Obstruction

Abstract: We present 2 cases demonstrating focal increased activity in the liver on 18F-fluorodeoxyglucose positron emission tomography scans resulting from central venous obstruction and increased blood flow to select regions of the liver via collateral veins. Collateral venous pathways from anterior chest wall veins to the portal veins can form via paraumbilical veins (including the vein of Burrow and the superior and inferior veins of Sappey) or subcapsular veins of the liver via musculophrenic vessels. Imagers shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…These include the internal thoracic vein to the portal vein via the umbilical or paraumbilical veins, leading to focal flow to the liver in the region of the falciform ligament ( 7 ). There are also the lateral thoracic veins, superficial veins, azygos-hemiazygos, and paravertebral collateral systems ( 6 , 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the internal thoracic vein to the portal vein via the umbilical or paraumbilical veins, leading to focal flow to the liver in the region of the falciform ligament ( 7 ). There are also the lateral thoracic veins, superficial veins, azygos-hemiazygos, and paravertebral collateral systems ( 6 , 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The differential for focally increased hepatic activity generally includes misregistration artifact from diaphragmatic motion and metabolic activity within the adjacent bowel (which had been confidently excluded in this case, as there was no evidence of misregistration, no nearby bowel activity of sufficient intensity to account for the hepatic finding, and the focal increased hepatic activity conformed to the shape of the liver in three planes and on the MIP, corresponding to the finding on CT) versus primary or secondary hepatic neoplasm, most likely metastatic lymphoma in this case. When interventional radiology (IR) was consulted for liver biopsy and reviewed the CT findings, IR strongly concurred with the CT interpretation favoring a benign etiology for the CT finding, which had been stable in size for three months, likely related to collateral blood flow, prompting the question, “Could the focal abnormal increased FDG uptake on PET also be due to collateral blood flow, rather than a hypermetabolic mass?” A literature search identified one published report in the thoracic imaging literature of focal liver uptake in this same region on FDG-PET in two lung cancer patients with SVC obstruction ( 1 ). Given the previously reported PET finding and the CT features favoring benignity of the lesion, liver biopsy was deferred in favor of CT followup, which thereafter documented stability of the hepatic finding for 14 months ( Fig.…”
Section: Case Reportmentioning
confidence: 99%
“…4,5 A literature search identified reports of 4 cases of false-positive FDG activity in the same region of the liver in SVCO. 1,[6][7][8] It was suggested that FDG PET study can be repeated using an IV injection site in the FIGURE 1. Above are the cross-sectional PET/CT series and MIP images (on the right) at the level of the liver dome acquired 60 minutes postinjection of FDG activity.…”
mentioning
confidence: 99%
“…This can result in contrast enhancement on CT or focal tracer activity on 99m Tc-sulfur colloid scintigraphy in medial left lobe of the liver near the falciform ligament 4,5 . A literature search identified reports of 4 cases of false-positive FDG activity in the same region of the liver in SVCO 1,6–8 . It was suggested that FDG PET study can be repeated using an IV injection site in the lower extremity 1,7 .…”
mentioning
confidence: 99%